Zero-Fluoroscopy Catheter Ablation of Supraventricular Tachycardias in the Pediatric Population - Mirko Topalović; Matevž Jan; Tine Prolič Kalinšek; David Žižek; Jernej Štublar; Rina Rus; Dimitrij Kuhelj (MDPI AG, 2023)
Catheter ablation (CA) of supraventricular tachycardias (SVTs) is conventionally performed with the aid of X-ray fluoroscopy. Usage of a three-dimensional (3D) electro-anatomical mapping (EAM) system and intracardiac echocardiography (ICE) enables zero-fluoroscopy ablation, eliminating the harmful effects of radiation. We retrospectively analyzed the feasibility, effectiveness and safety of zero-fluoroscopy radiofrequency and cryoablation of various types of SVTs in pediatric patients. Overall, in 171 consecutive patients (12.5 ± 3.9 years), 175 SVTs were diagnosed and 201 procedures were performed. The procedural success rate was 98% (193/197), or more precisely, 100% (86/86) for AVNRT, 95.8% (91/95) for AVRT, 94.1% (16/17) for AT and 100% (2/2) for AFL. No complications were recorded. Follow-up was complete in 100% (171/171) of patients. During the mean follow-up period of 488.4 ± 409.5 days, 98.2% of patients were arrhythmia-free with long-term success rates of 98.7% (78/79), 97.5% (78/80), 100% (13/13) and 100% (2/2) for AVNRT, AVRT, AT and AFL, respectively. Zero-fluoroscopy CA of various types of SVTs in the pediatric population is a feasible, effective and safe treatment option.